Menstimulasi Kemandirian Anak Autisme Melalui Pembelajaran Individual Berbasis Spiritual - Firdaus, Umi Risatul; Tumbularani, Tumbularani; Setyo, Bono (As-Sibyan: Jurnal Pendidikan Anak Usia Dini, 2024)
Autistic children often have difficulty living independently due to unstable brain function, to help stabilize their brain function, inner peace is needed by providing positive stimulation through spiritual habits to achieve inner and outer peace. This study aims to explain the stages of stimulating the independence of autistic children through spiritual-based individual learning, which is applied at the Pondok Perkampungan Ainul Yakin Gunung Kidul. This study uses a descriptive qualitative technique by collecting data through observation and interviews. Data were analyzed using the process of reduction, presentation, and conclusion. The study results indicate that spiritual habits can be used as an alternative to stimulate the independence of autistic children, such as the habit of praying, Islamic studies, and routine picket. This habit is adjusted to the class category and independence. This finding implies that spiritual habits can help autistic children become more independent, through the habit of developing themselves as perfect human beings created by God.